Novel divalent europium doped MgAlON transparent ceramic for shortwave ultraviolet erasable windows. (August 2015) - Liu, Xin; Wang, Hao; Tu, Bingtian; Wang, Weimin; Fu, Zhengyi
Abstract : A novel divalent europium ion doped UV erasable MgAlON (Mg0.27 Al2.58 O3.73 N0.27 ) transparent ceramic in which Eu/Al atom ratio is 0.25% was fabricated by pressureless sintering. The ceramic was highly dense with high transmittance in visible and infrared region and good mechanical properties. Due to the MgAlON host absorption and 4f–5d energy transfer of Eu 2+, a broad absorption band occurred in ultraviolet light region. The cathodoluminescence (CL) image revealed that the Eu 2+ ions were uniformly distributed in grain boundary.